Toward a standardized and individualized laboratory-based protocol for wheelchair-specific exercise capacity testing in wheelchair athletes: A scoping review - Janssen, R. J. F.; de Groot, S.; Van der Woude, L. H. V.; Houdijk, H.; Vegter, R. J. K. (American Journal of Physical Medicine & Rehabilitation, 2023)
Previous studies on handrim wheelchair-specific (an)aerobic exercise capacity in wheelchair athletes have used a diversity of participants, equipment, and protocols. Therefore, test results are difficult to compare among studies. The first aim of this scoping review is to provide an overview of the populations studied, the equipment and protocols used, and the reported outcomes from all laboratory-based studies on wheelchair-specific exercise capacity in wheelchair athletes. The second aim is to synthesize these findings into a standardized, yet individualized protocol. A scoping literature search resulted in 10 anaerobic and 38 aerobic protocols. A large variety in equipment, protocol design, and reported outcomes was found. Studies that systematically investigated the influence of protocol features are lacking, which makes it difficult to interpret and compare test outcomes among the heterogeneous group of wheelchair athletes. Protocol design was often dependent on a priori participant knowledge. However, specific guidelines for individualization were missing. However, the common protocol features of the different studies were united into guidelines that could be followed when performing standardized and individualized wheelchair-specific exercise capacity tests in wheelchair athletes. Together with guidelines regarding reporting of participant characteristics, used equipment, and outcome measures, we hope to work toward more international agreement in future testing.